2010
DOI: 10.1177/1090198110361315
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analytic Review of School-Based Prevention for Cannabis Use

Abstract: This investigation used meta-analytic techniques to evaluate the effectiveness of school-based prevention programming in reducing cannabis use among youth aged 12 to 19. It summarized the results from 15 studies published in peer-reviewed journals since 1999 and identified features that influenced program effectiveness. The results from the set of 15 studies indicated that these school-based programs had a positive impact on reducing students' cannabis use (d = 0.58, CI: 0.55, 0.62) compared to control conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 38 publications
3
78
1
6
Order By: Relevance
“…The program is based on the model for Life Skills education proposed by the World Health Organization (WHO 1997), and developmental psychological models on the etiology of youth problem behavior, as well as empirical findings on risk and protective factors for substance misuse (e.g., Petraitis et al 1995;Scheier 2010). IPSY is a comprehensive program that combines training in intrapersonal and interpersonal Life Skills (e.g., self-awareness, coping strategies, assertiveness, or communication skills) with instruction on substance-specific skills (e.g., resistance to peers offering substances) and the promotion of school bonding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The program is based on the model for Life Skills education proposed by the World Health Organization (WHO 1997), and developmental psychological models on the etiology of youth problem behavior, as well as empirical findings on risk and protective factors for substance misuse (e.g., Petraitis et al 1995;Scheier 2010). IPSY is a comprehensive program that combines training in intrapersonal and interpersonal Life Skills (e.g., self-awareness, coping strategies, assertiveness, or communication skills) with instruction on substance-specific skills (e.g., resistance to peers offering substances) and the promotion of school bonding.…”
Section: Methodsmentioning
confidence: 99%
“…This is particularly true for those based on the social influence approach, such as the social cognitive and comprehensive Life Skills programs. Finally, for the prevention of adolescent cannabis and other illicit drug use via school-based programs, Bühler and Thrul (2013), based on reviews by Porath-Waller et al (2010;15 RCT), and Faggiano et al (2008;29 RCT), concluded that programs relying on the social influence approach and those that promote competencies such as Life Skills programs are the most effective ones. Taken together, there is a body of research indicating that programs promoting competencies and skills, and based on the social influence approach (including Life Skill programs) can be effective intervention tools to combat substance use in adolescence.…”
Section: Introductionmentioning
confidence: 98%
“…Even when cannabis use is considered separately, these types of programs appear to be the most beneficial [80]. This is not as straightforward when targeting adolescents outside the school environment as evidence so far has been insufficient to support the efficacy of one model of intervention over another [79].…”
Section: Early Prevention and Intervention Programs For Cannabis Use mentioning
confidence: 90%
“…In the only meta-analytic review to date, Porath-Waller et al [80] explored 15 programs of schoolbased interventions for cannabis use and found that they had a positive effect in reducing cannabis use in young people aged 12-19 years compared to control conditions. They also reported that programs, which encouraged peer interaction, were more beneficial than those delivered in a didactic manner.…”
Section: Early Prevention and Intervention Programs For Cannabis Use mentioning
confidence: 97%
“…5 To help facilitate the increase in cannabis education, it will be important to focus on the strategic approach in delivery and the specific content to be addressed. Systematic reviews [8][9][10] have concluded that approaches to delivering cannabis content are more effective in reaching adolescents and limiting use when: digital-based (e.g., social media); facilitated by a non-teacher; frequent and factual; and peer and family member-engaging. Furthermore, applying scare tactics, the "just say no" approach, and over-assertions of cannabis' harms (e.g., emphasizing causation over risk) are cautioned against.…”
Section: Resultsmentioning
confidence: 99%